Red phosphorus-loaded carbon fiber material and application thereof in preparation of potassium ion battery

Porous carbon fiber materials were prepared by coaxial electrospinning method and loaded with red phosphorus nanoparticles, which solved the problem of poor circulation stability of red phosphorus negative electrode materials, and achieved efficient potassium storage electrochemical performance and long cycle life.

CN119877200APending Publication Date: 2025-04-25LANZHOU JIAOTONG UNIV

Patent Information

Application Number
CN202510305293.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The low conductivity and volume expansion of the red phosphorus negative electrode material in potassium ion batteries lead to poor cycle stability, which is difficult to meet the practical application needs.

Method used

Porous carbon fiber material is prepared by coaxial electrospinning method, and red phosphorus nanoparticles are loaded into the carbon fiber material by evaporation condensation method to form a three-dimensional porous carbon nanofiber negative electrode material modified by iron metal clusters.

Benefits of technology

The potassium storage electrochemical performance of the red phosphorus negative electrode is improved, the structural strength and cycle stability of the material are enhanced, the initial capacity is above 600 mAh/g, and the capacity can still be maintained above 50% after 200 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877200A_ABST
    Figure CN119877200A_ABST
Patent Text Reader

Abstract

The invention particularly relates to a red phosphorus-loaded carbon fiber material and application thereof in preparation of a potassium ion battery. The method comprises the following steps: dissolving polyacrylonitrile, ferric acetylacetonate and ZIF-8 in N, N-dimethylformamide to prepare a shell solution; dissolving potassium hydroxide in dimethyl sulfoxide to obtain a core solution; spinning the shell solution and the core solution into a nano composite fiber membrane through coaxial electrostatic spinning; carrying out pre-oxidation and carbonization treatment on the nano composite fiber membrane to obtain a uniform porous carbon nano fiber membrane loaded with iron metal clusters under proper atmosphere and temperature; and introducing red phosphorus into pores of the carbon nanofiber membrane by using an evaporation-condensation method to obtain the red phosphorus negative electrode material loaded with the iron metal cluster. The red phosphorus is nanocrystallized and embedded into the porous carbon fiber matrix, so that the problem of volume change of the red phosphorus is effectively solved; and meanwhile, the activation process is simplified by utilizing a coaxial electrostatic spinning technology, and the potassium storage electrochemical performance of the red phosphorus negative electrode is remarkably improved by introducing metal clusters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials for potassium ion batteries, and in particular to a carbon fiber material loaded with red phosphorus, a method for preparing the material, and application of the material as a negative electrode in preparing a potassium ion battery. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Potassium-ion batteries (KIBs) are considered as a potential alternative to lithium-ion batteries (LIBs) due to their higher energy density and cost-effectiveness, especially for large-scale energy storage. + ) The large ionic radius (1.38 Å) leads to a slow migration speed during the insertion / deinsertion process, which accelerates the damage of the electrode material and severely limits the practical application of KIBs. Therefore, one of the primary challenges of KIBs is to develop reliable electrode materials, especially negative electrode materials with stability, high activity and good structural strength.

[0004] As a cheap anode material, red phosphorus (Red P) has shown a very high theoretical capacity based on alloying / alloying mechanism and appropriate redox potential, and has the potential to achieve ultra-high energy density. However, the low conductivity (10 - 14 S cm -1 ) and its + The volume expansion during the insertion / removal process seriously affects its cycle stability, making it difficult to meet the needs of practical applications. In addition, the energy storage mechanism of red phosphorus is similar to that of sulfur, and polyphosphide molecules are produced during the reaction. These polyphosphides bind to the solvent through strong interactions, resulting in a shuttle effect, which in turn causes a series of problems such as loss of active phosphorus and electrode corrosion.

[0005] Therefore, designing and preparing a porous carbon matrix that can effectively accommodate red phosphorus nanoparticles to alleviate the volume expansion effect has important scientific significance and practical value for improving the potassium storage electrochemical performance of the red phosphorus negative electrode. Summary of the invention

[0006] In view of the shortcoming that the current activated pore-forming agent is difficult to act evenly on the flexible fiber membrane, the present invention is designed to provide a coaxial electrospinning self-supporting negative electrode material that can be applied to potassium ion batteries. Based on a simple one-step sintering method, the material can quickly and effectively prepare a uniform microporous structure on the surface of the carbon material, providing a stable loading space for red phosphorus nanoparticles, and has the potential for industrial large-scale production.

[0007] Based on the above effects, the present invention provides the following technical solutions: In a first aspect, the present invention provides a carbon fiber material loaded with red phosphorus. The material is based on a self-supporting flexible composite carbon fiber membrane as a matrix, and red phosphorus elements are loaded inside the carbon fiber membrane through physical adsorption and chemical surface reaction.

[0008] The above-mentioned carbon fiber material first obtains a matrix carbon fiber material by electrostatic spinning, so that the material is a self-supporting, flexible material that can be arbitrarily cut to suit work needs. In addition, the carbon fiber membrane prepared by spinning has a rich porous structure, which is beneficial to improving its electrochemical performance as a potassium ion negative electrode on the one hand, and on the other hand, it also provides a rich attachment site for the load of red phosphorus. In view of the defects of red phosphorus such as low conductivity and polyphosphide dissolution, the present invention achieves good rate performance and long cycle life through the optimization strategy of red phosphorus-carbon fiber membrane composite, with an initial capacity of more than 600 mAh / g, and the capacity can still be maintained at more than 50% after 200 cycles.

[0009] The second aspect of the present invention provides a method for preparing the red phosphorus-loaded carbon fiber material according to the first aspect, comprising the following steps: (1) Nanocomposite fiber membranes were prepared by coaxial electrospinning using 2-methylimidazole zinc salt (ZIF-8), iron salt, and polymer dissolved in N,N-dimethylformamide as the shell solution and alkaline dimethyl sulfoxide as the core solution; (2) sintering the nanocomposite fiber membrane prepared in step (1) in an oxygen-free environment to obtain a porous carbon nanofiber membrane; (3) The porous carbon nanofiber membrane prepared in step (2) is heated and annealed together with red phosphorus in a vacuum environment to obtain a porous carbon nanofiber membrane.

[0010] In step (1), there are the following preferred solutions: The iron salt is preferably an organic iron compound. In one embodiment of the present invention, the iron salt is ferric acetylacetonate. The polymer is preferably a polymer that can be used to prepare flexible spinning materials, including but not limited to polyester, polyamide, polyvinyl alcohol, polyacrylonitrile, etc.

[0011] In one embodiment verified by the present invention, the shell solution is prepared as follows: 0.20-0.30 g ZIF-8, 0.07-0.15 g ferric acetylacetonate, and 1.00-1.50 g polyacrylonitrile are dissolved in 8-15 ml N,N-dimethylformamide to fully disperse them and obtain a shell solution.

[0012] The core solution is preferably prepared by mixing an inorganic base with dimethyl sulfoxide, wherein the inorganic base is such as sodium hydroxide, potassium hydroxide or calcium hydroxide. In one embodiment verified by the present invention, the inorganic base is potassium hydroxide. The core solution is prepared as follows: 0.35-0.60 g of potassium hydroxide is added to 8-15 ml of dimethyl sulfoxide and heated at 55-65° C. for 10-12 days to completely dissolve it.

[0013] The coaxial electrospinning is carried out by coaxially arranged inner and outer needles, wherein the outer needle is connected to the shell solution, and has an inner diameter of 0.95-1.10 mm and an outer diameter of 1.4-2.0 mm; the inner needle is connected to the core solution, and has an inner diameter of 0.3-0.5 mm and an outer diameter of 0.6-0.8 mm; the propulsion speed of the shell solution and the core solution are both 0.06-0.10 mm / min, the lateral translation speed is 280-350 mm / min, the roller receiving speed is 8-15 r / min, the open circuit voltage is positive 13-17 KV, and the negative pressure is -3--1 KV.

[0014] In the above step (2), the sintering procedure is as follows: the nanocomposite fiber membrane is heated to 210-250°C for 3-4 hours, then placed in an argon environment and heated to 860-920°C at 4-6°C / min, and sintered for 1.8-3 hours to obtain a porous carbon nanofiber membrane. The nanocomposite fiber membrane is subjected to high-temperature heat treatment in an argon environment, the central atoms of the ZIF-8 metal framework in the shell layer are volatilized to form a macroporous structure, the acetylacetonate iron is reduced to iron metal clusters, and the potassium hydroxide activator in the core layer can generate a large number of micropores on the internal structure of the fiber, thereby obtaining a hierarchical porous structure flexible carbon fiber material loaded with metal clusters.

[0015] In the above step (3), red phosphorus is infiltrated into the pores of the carbon material by evaporation and condensation, and finally a three-dimensional porous carbon nanofiber-loaded red phosphorus nanoparticle composite material modified by iron metal clusters is obtained. The mass ratio of the porous carbon nanofiber membrane to the red phosphorus is 1:1.5-3, and the more preferred ratio is 1:2; the heating and annealing method is as follows: the porous carbon nanofiber membrane and the red phosphorus are encapsulated in a vacuum quartz tube, heated to 850-900°C at 8-12°C / min, and kept warm for 7-10 h, then cooled to 250°C at 0.8-1.5°C / min, and kept warm for 22-26 h, and finally cooled to room temperature to obtain the obtained composite material.

[0016] In a third aspect, the present invention provides use of the above-mentioned red phosphorus-loaded carbon fiber material in the preparation of a potassium ion battery.

[0017] According to a fourth aspect of the present invention, a negative electrode of a potassium ion battery is provided, wherein the negative electrode is the red phosphorus-loaded carbon fiber material according to the first aspect.

[0018] According to a fifth aspect of the present invention, a potassium ion battery is provided, wherein the battery has the negative electrode described in the fourth aspect.

[0019] In a specific embodiment, the potassium ion battery is a button type, and the assembly method is as follows: the material described in the first aspect is used as the negative electrode, potassium metal is used as the positive electrode, glass fiber is used as the separator, and potassium bis(fluorosulfonyl)imide (KFSI) ethylene carbonate (EC) / diethyl carbonate (DEC) solution is used as the electrolyte; in the electrolyte, the volume ratio of EC to DEC is 1:0.8~1.2, and the concentration of KFSI is 3.5~4.5mol / L.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes the evaporation-condensation method to introduce red phosphorus into the pores of the carbon nanofiber membrane to obtain a red phosphorus negative electrode material loaded with iron metal clusters. By nano-sizing the red phosphorus and embedding it into a porous carbon fiber matrix, the problem of large volume change of red phosphorus is effectively overcome. At the same time, the coaxial electrospinning technology is used to simplify the activation process, and the introduction of metal clusters significantly improves the potassium storage electrochemical performance of the red phosphorus negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 The morphology characterization results of the red phosphorus loaded carbon fibers in Example 1; in, Figure 1 A is the plane SEM image of the carbon material obtained after coaxial electrospinning. Figure 1 B is a cross-sectional SEM image.

[0023] Figure 2 Electrochemical performance of the potassium ion battery assembled in Example 1; Figure 2 (a) is the charge and discharge curve of the potassium ion battery assembled in Example 1 at a current density of 0.1 A / g for the first three cycles; Figure 2 (b) Cyclic performance of the potassium ion battery assembled in Example 1 at a current density of 0.1 A / g; Figure 2 (c) Cycling performance of the potassium ion battery assembled in Example 1 at a current density of 1 A / g.

[0024] Figure 3 Electrochemical performance of the potassium ion battery assembled in Comparative Example 1; Figure 3(a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 1 at a current density of 0.1 A / g; Figure 3 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 1 at a current density of 0.1 A / g; Figure 3 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 1 at a current density of 1 A / g.

[0025] Figure 4 Electrochemical performance of the potassium ion battery assembled in Comparative Example 2; Figure 4 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 2 at a current density of 0.1 A / g; Figure 4 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 2 at a current density of 0.1 A / g; Figure 4 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 2 at a current density of 1 A / g.

[0026] Figure 5 Electrochemical performance of the potassium ion battery assembled in Comparative Example 3; Figure 5 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 3 at a current density of 0.1 A / g; Figure 5 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 3 at a current density of 0.1 A / g; Figure 5 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 3 at a current density of 1 A / g.

[0027] Figure 6 Electrochemical performance of the potassium ion battery assembled in Comparative Example 4; Figure 6 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 4 at a current density of 0.1 A / g; Figure 6 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 4 at a current density of 0.1 A / g; Figure 6 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 4 at a current density of 1 A / g.

[0028] Figure 7 Electrochemical performance of the potassium ion battery assembled in Comparative Example 5; Figure 7 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 5 at a current density of 0.1 A / g; Figure 7 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 5 at a current density of 0.1 A / g; Figure 7 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 5 at a current density of 1 A / g.

[0029] Figure 8 Electrochemical performance of the potassium ion battery assembled in Comparative Example 6; Figure 8 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 6 at a current density of 0.1 A / g; Figure 8 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 6 at a current density of 0.1 A / g; Figure 8 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 6 at a current density of 1 A / g.

[0030] Fig. 9 Electrochemical performance of the potassium ion battery assembled in Comparative Example 7; Fig. 9 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 7 at a current density of 0.1 A / g; Fig. 9 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 7 at a current density of 0.1 A / g; Fig. 9 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 7 at a current density of 1 A / g.

[0031] Fig.10 Electrochemical performance of the potassium ion battery assembled in Comparative Example 8; Fig.10 (a) is the charge and discharge curve of the first three cycles of the potassium ion battery assembled in Comparative Example 8 at a current density of 0.1 A / g; Fig.10 (b) Cyclic performance of the potassium ion battery assembled in Comparative Example 8 at a current density of 0.1 A / g; Fig.10 (c) Cycling performance of the potassium ion battery assembled in Comparative Example 8 at a current density of 1 A / g. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific examples. The red phosphorus used in the following examples and comparative examples is commercial red phosphorus, which can be purchased through commercial channels.

[0035] Example 1 In this embodiment, a highly conductive hierarchical porous carbon fiber with iron metal clusters is prepared by coaxial electrospinning, and then red phosphorus is loaded into the carbon matrix by evaporation condensation to prepare a red phosphorus negative electrode material suitable for potassium ion batteries. Specifically, the following steps are included: (1) 0.25 g ZIF-8 and 0.09 g ferric acetylacetonate were mixed with 1.05 g polyacrylonitrile, and the mixture was dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.42 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, and the mixture was heated and stirred at 60°C for 10 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle, wherein the coaxial needle comprises an inner needle and an outer needle arranged coaxially, the inner needle has an inner diameter of 0.4 mm and an outer diameter of 0.7 mm, the outer needle has an inner diameter of 1.05 mm and an outer diameter of 1.5 mm, the shell solution is connected to the outer needle, and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.07 mm / min, the lateral translation speed of the syringe is 300 mm / min, the roller receiving speed is 10 r / min, the open circuit voltage is 15 KV positive, and the negative pressure is -2KV. After the electrospinning is completed, a nanocomposite fiber membrane is obtained; (3) The composite fiber membrane was heated to 220°C in a muffle furnace for 2 h, and then placed in an argon gas environment and heated to 900°C at a rate of 5°C / min and sintered for 2 h to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters; (4) The porous carbon nanofiber membrane and commercial red phosphorus were packaged together in a vacuum quartz tube in a mass ratio of 1:2, heated to 898 °C at 10 °C / min, and kept warm for 8 h. Then the temperature was cooled to 260 °C at 1 °C / min, kept warm for another 24 h, and finally cooled to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus negative electrode material.

[0036] The obtained carbon fiber loaded with red phosphorus was characterized and analyzed, such as Figure 1 As shown, the left picture is a planar SEM image of the carbon material obtained after coaxial electrospinning, and the right picture is a cross-sectional SEM image, both of which can confirm that the material is a nanoscale fiber structure.

[0037] The obtained self-supporting negative electrode material was cut into 10 mm wide square pieces and assembled with potassium metal into a button battery. The battery uses glass fiber as a separator and KFSI is dissolved in EC / DEC (volume ratio of 1:1) solvent as an electrolyte with a concentration of 4 mol / L.

[0038] Figure 2 The charge and discharge curves (a) of the assembled potassium ion battery at the current density of 0.1A / g for the first three cycles and the cycle performance (bc) at the current density of 0.1A / g and 1A / g. It can be seen from the figure that at the current density of 0.1A / g, the battery has an initial specific capacity of 690 mAh / g, and the capacity is maintained at 528 mAh / g after 50 cycles. At the current density of 1A / g, the battery has an initial specific capacity of 402 mAh / g, and the capacity is maintained at 313 mAh / g after 200 cycles.

[0039] Example 2 In this embodiment, another method for preparing a self-supporting flexible carbon fiber composite red phosphorus negative electrode material is provided, comprising the following steps: (1) 0.30 g ZIF-8 and 0.15 g ferric acetylacetonate were mixed with 1.50 g polyacrylonitrile, and the mixture was dissolved in 15 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.60 g potassium hydroxide was added to 15 ml dimethyl sulfoxide solution, and the mixture was heated and stirred at 65°C for 12 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle, wherein the coaxial needle comprises an inner needle and an outer needle arranged coaxially, the inner needle has an inner diameter of 0.5 mm and an outer diameter of 0.8 mm, the outer needle has an inner diameter of 1.10 mm and an outer diameter of 2.0 mm, the shell solution is connected to the outer needle, and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.10 mm / min, the lateral translation speed of the syringe is 350 mm / min, the roller receiving speed is 15 r / min, the open circuit voltage is 17 KV positive, and the negative pressure is -3 KV. After the electrospinning is completed, a nanocomposite fiber membrane is obtained; (3) The composite fiber membrane was heated to 250°C in a muffle furnace for 3 h, then placed in an argon gas environment and heated to 920°C at 6°C / min and sintered for 1.8 h to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters; (4) The porous carbon nanofiber membrane and commercial red phosphorus were packaged together in a vacuum quartz tube in a mass ratio of 1:3, heated to 900°C at 12°C / min, and kept warm for 7 h. Then the temperature was cooled to 250°C at 1.5°C / min, kept warm for another 22 h, and finally cooled to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus negative electrode material.

[0040] Example 3 In this embodiment, another method for preparing a self-supporting flexible carbon fiber composite red phosphorus negative electrode material is provided, comprising the following steps: (1) 0.20 g ZIF-8 and 0.07 g ferric acetylacetonate were mixed with 1.00 g polyacrylonitrile, and the mixture was dissolved in 8 ml N,N-dimethylformamide and stirred until completely dissolved to obtain a shell solution; 0.350 g potassium hydroxide was added to 8 ml dimethyl sulfoxide solution, and the mixture was heated at 55°C and stirred for 12 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle, wherein the coaxial needle comprises an inner needle and an outer needle arranged coaxially, the inner needle has an inner diameter of 0.3 mm and an outer diameter of 0.6 mm, the outer needle has an inner diameter of 0.95 mm and an outer diameter of 1.4 mm, the shell solution is connected to the outer needle, and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.06 mm / min, the lateral translation speed of the syringe is 280 mm / min, the roller receiving speed is 8 r / min, the open circuit voltage is 13 KV positive, and the negative pressure is -1 KV. After the electrospinning is completed, a nanocomposite fiber membrane is obtained; (3) The composite fiber membrane was heated to 210°C in a muffle furnace for 4 h, then placed in an argon gas environment and heated to 860°C at a rate of 4°C / min and sintered for 3 h to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters; (4) The porous carbon nanofiber membrane and commercial red phosphorus were packaged together in a vacuum quartz tube at a mass ratio of 1:1.5, heated to 850 °C at 8 °C / min, and kept warm for 10 h. Then the temperature was cooled to 250 °C at 0.8 °C / min, kept warm for another 26 h, and finally cooled to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus negative electrode material.

[0041] Comparative Example 1 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Embodiment 1 is that step (1) is performed as follows: 0.25 g ZIF-8 and 1.05 g polyacrylonitrile were mixed and dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution. 0.42 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, heated and stirred at 60° C. for 10 days to dissolve the potassium hydroxide to obtain a core solution.

[0042] Figure 3 The assembled potassium ion battery is shown in the figure below: The charge and discharge curves of the first three cycles at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). As can be seen from the figure, at a current density of 0.1A / g, the battery has an initial specific capacity of 444 mAh / g, and the capacity is maintained at 358 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 250 mAh / g, and the capacity is maintained at 179 mAh / g after 200 cycles. The material prepared in this embodiment has no metal cluster components, which causes the loss of active phosphorus and electrode corrosion, thereby affecting the cycle performance. The corresponding battery capacity is lower than that in Example 1.

[0043] Comparative Example 2 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Embodiment 1 is that step (1) is performed as follows: 0.25 g ZIF-8, 0.09 g ferric acetylacetonate and 1.05 g polyacrylonitrile were mixed and dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.21 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, heated and stirred at 60° C. for 10 days to dissolve the potassium hydroxide to obtain a core solution.

[0044] Figure 4 The assembled potassium ion battery has the charge and discharge curves of the first three cycles at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). It can be seen from the figure that at a current density of 0.1A / g, the battery has an initial specific capacity of 652 mAh / g, and the capacity is maintained at 489 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 333 mAh / g, and the capacity is maintained at 221 mAh / g after 200 cycles. The material prepared in this embodiment has a low content of potassium hydroxide activator, insufficient pore formation, and the failure of red phosphorus to fully penetrate affects the subsequent battery performance, making it difficult to exert the activation effect, and the corresponding battery capacity is lower than that in Example 1.

[0045] Comparative Example 3 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Embodiment 1 is that step (1) is performed as follows: 0.25 g ZIF-8 and 0.09 g ferric acetylacetonate were mixed with 1.05 g polyacrylonitrile, dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.63 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, heated at 60° C. and stirred for 10 days to dissolve the potassium hydroxide to obtain a core solution.

[0046] Figure 5 The assembled potassium ion battery has the charge and discharge curves of the first three cycles at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). It can be seen from the figure that at a current density of 0.1A / g, the battery has an initial specific capacity of 562 mAh / g, and the capacity is maintained at 456 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 333 mAh / g, and the capacity is maintained at 312 mAh / g after 200 cycles. The material prepared in this embodiment has a high content of potassium hydroxide activator, and the excessively high pore content causes part of the carbon skeleton to collapse, making it difficult to exert the activation effect, affecting the subsequent battery performance, and the corresponding battery capacity is lower than that in Example 1.

[0047] Comparative Example 4 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Embodiment 1 is that step (1) is performed as follows: 0.25 g ZIF-8 and 0.09 g ferric acetylacetonate were mixed with 0.82 g polyacrylonitrile, dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.42 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, heated at 60° C. and stirred for 10 days to dissolve the potassium hydroxide to obtain a core solution.

[0048] Figure 6 The assembled potassium ion battery is shown in the charge and discharge curves of the first three cycles at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). It can be seen from the figure that at a current density of 0.1A / g, the battery has an initial specific capacity of 566 mAh / g, and the capacity is maintained at 424 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 316 mAh / g, and the capacity is maintained at 288 mAh / g after 200 cycles. The material prepared in this embodiment has a low content of polyacrylonitrile, and the solution viscosity is insufficient to form filaments during the electrospinning process. The mechanical strength of the fiber is insufficient and the fiber cannot form a complete porous network structure after carbonization, thereby reducing the conductivity and energy storage performance, and the corresponding battery capacity is lower than that of Example 1.

[0049] Comparative Example 5 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Embodiment 1 is that step (1) is performed as follows: 0.25 g ZIF-8 and 0.09 g ferric acetylacetonate were mixed with 1.29 g polyacrylonitrile, dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.42 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, heated at 60° C. and stirred for 10 days to dissolve the potassium hydroxide to obtain a core solution.

[0050] Figure 7 The assembled potassium ion battery has the charge and discharge curves of the first three cycles at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). It can be seen from the figure that at a current density of 0.1A / g, the battery has an initial specific capacity of 392 mAh / g, and the capacity is maintained at 312 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 289 mAh / g, and the capacity is maintained at 233 mAh / g after 200 cycles. The material prepared in this embodiment has a high content of polyacrylonitrile, increased solution viscosity, and unstable spinning. The increase in fiber diameter leads to the formation of a dense structure after fiber carbonization, which inhibits porosity, is not conducive to the loading and performance improvement of red phosphorus, and affects the subsequent battery performance. The corresponding battery capacity is lower than that of Example 1.

[0051] Comparative Example 6 In this embodiment, another highly conductive hierarchical porous carbon fiber prepared by coaxial electrospinning is provided, which is different from Example 1 in that the obtained self-supporting negative electrode material is cut into square pieces with a width of 10 mm and assembled with potassium metal into a button battery. The battery uses glass fiber as a separator, and KFSI is dissolved in EC / DEC (volume ratio of 1:1) solvent as an electrolyte with a concentration of 1 mol / L.

[0052] Figure 8 The assembled potassium ion battery shows the charge and discharge curves of the first three cycles at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). As can be seen from the figure, at a current density of 0.1A / g, the battery has an initial specific capacity of 670.64 mAh / g, and the capacity is maintained at 415 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 287 mAh / g, and the capacity is maintained at 239 mAh / g after 200 cycles. The material prepared in this embodiment has a relatively dilute electrolyte concentration, the formed SEI is uneven and not dense, the ion transport is slow, and the electrolyte decomposition is aggravated, which affects the subsequent battery performance, and the corresponding battery capacity is lower than that of Example 1.

[0053] Comparative Example 7 In this embodiment, another highly conductive hierarchical porous carbon fiber prepared by coaxial electrospinning is provided, which is different from Example 1 in that the obtained self-supporting negative electrode material is cut into square pieces with a width of 10 mm and assembled with potassium metal into a button battery. The battery uses glass fiber as a separator, and KPF6 is dissolved in EC / DEC (volume ratio of 1:1) solvent as an electrolyte with a concentration of 1 mol / L.

[0054] Fig. 9 The assembled potassium ion battery is shown in the first three charge and discharge curves (a) at a current density of 0.1A / g and the cycle performance (bc) at current densities of 0.1A / g and 1A / g. As can be seen from the figure, at a current density of 0.1A / g, the battery has an initial specific capacity of 302 mAh / g, and the capacity is maintained at 215 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 360 mAh / g, and the capacity is maintained at 253 mAh / g after 200 cycles. In the battery prepared in this embodiment, the solubility of KPF6 electrolyte in the electrolyte solvent is lower than that of KFSI electrolyte, resulting in a lower potassium ion concentration. At the same time, the ion pair effect of F⁻ and SI⁻ ions in the solvent is weak, which is conducive to the free migration of potassium ions. The PF6⁻ ions in KPF6 are relatively difficult to form a stable structure at the electrode / electrolyte interface, which in turn affects the performance of the battery, so the capacity of the battery is lower than that in Example 1.

[0055] Comparative Example 8 In this embodiment, a highly conductive hierarchical porous carbon fiber with iron metal clusters is prepared by coaxial electrospinning, and then red phosphorus is loaded into the carbon matrix by evaporation condensation to prepare a red phosphorus negative electrode material suitable for potassium ion batteries. Specifically, the following steps are included: (1) 0.25 g ZIF-8 and 0.09 g ferric acetylacetonate were mixed with 1.05 g polyacrylonitrile, and the mixture was dissolved in 10 ml N,N-dimethylformamide and stirred evenly until completely dissolved to obtain a shell solution; 0.42 g potassium hydroxide was added to 10 ml dimethyl sulfoxide solution, and the mixture was heated and stirred at 60°C for 10 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle, wherein the coaxial needle comprises an inner needle and an outer needle arranged coaxially, the inner needle has an inner diameter of 0.4 mm and an outer diameter of 0.7 mm, the outer needle has an inner diameter of 1.05 mm and an outer diameter of 1.5 mm, the shell solution is connected to the outer needle, and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.07 mm / min, the lateral translation speed of the syringe is 300 mm / min, the roller receiving speed is 10 r / min, the open circuit voltage is 15 KV positive, and the negative pressure is -2KV. After the electrospinning is completed, a nanocomposite fiber membrane is obtained; (3) The composite fiber membrane was heated to 220°C in a muffle furnace for 2 h, and then placed in an argon gas environment and heated to 900°C at a rate of 5°C / min and sintered for 2 h to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters; (4) The porous carbon nanofiber membrane and commercial red phosphorus were packaged together in a vacuum quartz tube in a mass ratio of 1:2, heated to 898 °C at 10 °C / min, and kept warm for 8 h. Then the temperature was cooled to 260 °C at 1 °C / min, kept warm for another 24 h, and finally cooled to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus negative electrode material.

[0056] The obtained self-supporting negative electrode material was cut into 10 mm wide square pieces and assembled with potassium metal into a button battery. The battery uses glass fiber as a separator and KPF6 dissolved in EC / DEC (volume ratio of 1:1) solvent as an electrolyte with a concentration of 4 mol / L.

[0057] Fig.10 The assembled potassium ion battery is shown in the first three charge and discharge curves at a current density of 0.1A / g (a) and the cycle performance at current densities of 0.1A / g and 1A / g (bc). It can be seen from the figure that at a current density of 0.1A / g, the battery has an initial specific capacity of 491 mAh / g, and the capacity is maintained at 383 mAh / g after 50 cycles. At a current density of 1A / g, the battery has an initial specific capacity of 253 mAh / g, and the capacity is maintained at 178 mAh / g after 200 cycles. In the battery prepared in this embodiment, the hexafluorophosphate ions (PF6⁻) in the high-concentration KPF6 electrolyte are closely paired with potassium ions (K⁺), the ion migration rate is slow, and the side reactions of PF6⁻ ions with electrode materials are more significant, resulting in a decrease in the charge and discharge rate and overall performance of the battery, so its battery capacity is lower than that of Example 1.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Application of red phosphorus-loaded carbon fiber material in the preparation of potassium ion batteries, characterized in that: The preparation method of the red phosphorus loaded carbon fiber material is as follows: (1) 0.20-0.30 g ZIF-8, 0.07-0.15 g ferric acetylacetonate, and 1.00-1.50 g polyacrylonitrile were dissolved in 8-15 ml N,N-dimethylformamide to fully disperse them and obtain a shell solution. 0.35-0.60 g potassium hydroxide was added to 8-15 ml dimethyl sulfoxide and heated at 55-65 °C for 10-12 days to completely dissolve them to obtain a core solution, and the core solution was coaxially electrospun to prepare a nanocomposite fiber membrane. (2) sintering the nanocomposite fiber membrane obtained in step (1) in an oxygen-free environment to obtain a porous carbon nanofiber membrane; (3) The porous carbon nanofiber membrane obtained in step (2) is heated and annealed together with red phosphorus in a vacuum environment to obtain a porous carbon nanofiber membrane.

2. The use of the red phosphorus loaded carbon fiber material in the preparation of a potassium ion battery as claimed in claim 1, characterized in that: In step (1), the coaxial electrospinning is carried out by coaxially arranged inner and outer needles, wherein the outer needle is connected to the shell solution, and has an inner diameter of 0.95~1.10 mm and an outer diameter of 1.4~2.0 mm; the inner needle is connected to the core solution, and has an inner diameter of 0.3~0.5 mm and an outer diameter of 0.6~0.8 mm; the propulsion speed of the shell solution and the core solution are both 0.06~0.10 mm / min, the lateral translation speed is 280~350 mm / min, the roller receiving speed is 8~15 r / min, the open circuit voltage is positive 13~17 KV, and the negative pressure is -3~-1 KV.

3. The use of the red phosphorus loaded carbon fiber material in the preparation of a potassium ion battery as claimed in claim 1, characterized in that: In step (2), the sintering procedure is as follows: the nanocomposite fiber membrane is heated to 210-250°C and kept warm for 3-4 h, then placed in an argon environment and heated to 860-920°C at a rate of 4-6°C / min, and sintered for 1.8-3 h to obtain a porous carbon nanofiber membrane.

4. The use of the red phosphorus loaded carbon fiber material in the preparation of a potassium ion battery as claimed in claim 1, characterized in that: In step (3), the mass ratio of the porous carbon nanofiber membrane to the red phosphorus is 1:1.5-3; the heating and annealing method is as follows: the porous carbon nanofiber membrane and the red phosphorus are packaged together in a vacuum quartz tube, heated to 850-900°C at 8-12°C / min, and kept warm for 7-10 h, then cooled to 250°C at 0.8-1.5°C / min, kept warm for 22-26 h, and finally cooled to room temperature.

5. A negative electrode of a potassium ion battery, characterized in that The negative electrode comprises a carbon fiber material loaded with red phosphorus, which is prepared by the preparation method described in any one of claims 1 to 4.

6. A potassium ion battery, characterized in that: The battery comprises the negative electrode according to claim 5.

7. The potassium ion battery according to claim 6, characterized in that: The potassium ion battery is a button-type battery, and the assembly method is as follows: potassium metal is used as the positive electrode, glass fiber is used as the separator, and KFSI EC / DEC solution is used as the electrolyte. In the electrolyte, the volume ratio of EC to DEC is 1:0.8~1.2, and the concentration of KFSI is 3.5~4.5mol / L.

Citation Information

Patent Citations

  • Porous nanotube or nanofiber type ZnO / ZnFe2O4 composite photocatalyst and electrostatic spinning one-step preparation method thereof

    CN106345479A

  • Method for preparing dual-layer porous carbon nano-fibers for lithium-sulfur battery and method for preparing cathode material by utilizing dual-layer porous carbon nano-fibers

    CN106848314A

  • Lithium ion battery diaphragm and preparation method thereof

    CN112751141A

  • Surface-activated multi-channel carbon nanofiber and preparation method thereof, composite metal material and battery negative electrode

    CN115172730A

  • Preparation method of porous interconnected hollow carbon nanofiber membrane

    CN117046319A

Cited By

  • Iron cluster loaded porous carbon fiber composite material as well as preparation method and application thereof

    CN120376627A

  • An iron cluster-loaded porous carbon fiber composite material and its preparation method and application

    CN120376627B